Exploring Procedural Content Generation of Environments for Virtual Museums: A Mixed-Initiative Approach - Claudio Rubio; Nicolas A. Barriga; Ben Ingram; Huizilopoztli Luna-García; Felipe Besoain (Heritage)
Cultural heritage preservation and dissemination face significant challenges in the digital era, particularly in artifact representation, visitor experience personalization, and virtual exploration scalability. This paper presents a tool for the development of a virtual museum, introducing a new system that addresses the challenges of the design and arrangement of the virtual environment process with two integrated stages: (1) Museum Generator, a procedural tool for creating realistic and adaptable virtual museum environments and (2) Artwork Arrangement, an automated system that optimizes the placement of artifacts based on thematic and spatial considerations. The system is validated through a Grid Search Method experiment that seeks to identify the combination of genetic operators that maximizes performance in arranging artworks in a virtual museum and evaluate how modifications to these operators affect the performance of different evolutionary executions. Results indicate that the proposed approach provides an effective and scalable solution for contributing to the design and arrangement of a virtual environment for museums, fostering greater accessibility to cultural heritage and delivering personalized visitor experiences.